The Investigation of Area of Median Nerve with Magnetic Resonance imaging - Aluçlu, Mustafa Arif; Aluçlu, Mehmet Ufuk (Fırat University, 2005)
Aims: Two questions are reminded that one is "Is carpal tunnel's volume/area increasing to cause narrowing median nerve by aging?", and the other one is "Can be median nerve impressed by surrounded tissues by aging?". In our study the area of median nerve was measured in the sections of magnetic resonance imaging. This study was made to determine if the area of median nerve would increase by aging which can be a reason of carpal tunnel syndrome. Materials and Methods: Our study was made only among women by seperating two groups. Group I was formed women in 20-45 whose average age was 35,1; Group II was formed women in 46+ whose average age was 56,0. Magnetic resonance images of volunteers were taken. The thickness of slices was 3 mm. The slices were continued from distal of radius and ulna to the proximal of the metacarpal bones. The inlet of the tunnel was accepted the last slice that showed the styloid process of ulna with scaphoid bone and pisiform bone; the outlet of the tunnel was accepted the slice of hamate bone with hamulus. Areas of the tunnel and the median nerve between the inlet and outlet of the tunnel were measured via computer in approximately six slices. Results: We calculated the areas of median nerve 10,26 mm2 in Group I and 10,32 mm2 in Group II. Conclusion: According to this result, we think that the area of median nerve is not increased by aging and the impressing of median nerve can have other possible reasons.©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç:Karpal tünel sendromunun daha çok yaşlı bayanlarda görülmesi akla iki soruyu getirmektedir. 1) Karpal tünel hacmi/alanı yaşlanmayla birlikte artıp mediyan siniri daraltır mı?; 2) Mediyan sinir hacmi/alanı yaşlanmayla birlikte artıp çevre dokular tarafından bası altında kalabilir mi? Çalışmamızda manyetik rezonans görüntüleme kesitlerinde mediyan sinir alanları ölçülmüştür. Bu çalışma karpal tünel sendromunun sebebi olabilecek mediyan sinir alanının yaşla birlikte artıp artmadığını belirlemek için yapılmıştır. Gereç ve Yöntem: Çalışmamız sadece kadınlar arasında ve iki gruba ayrılarak yapıldı. Grup I, 20-45 yaşlar arasında, yaş ortalaması 35,1 olan (n=10); Grup II ise 46 yaş üstü, yaş ortalaması 56,0 olan (n=10) kadınlardan oluşmaktaydı. Gönüllülerin manyetik rezonans görüntüleri alındı. Dilimlerin kalınlığı 3 mm idi. Dilimler radius ve ulnanın distalinden metakarpal kemiklerin proksimaline kadar devam etmekteydi. Tünelin girişi olarak ulnanın processus styloideus'u ile birlikte skafoid ve pisiform kemiğin görüldüğü son dilim; tünelin çıkışı olarak hamatum kemiğinin çengelinin görüldüğü dilim kabul edildi. Tünelin girişi ve çıkışı arasındaki ortalama altı dilimde mediyan sinirin alanları bilgisayar yoluyla ölçüldü. Bulgular: Grup I'de mediyan sinir alanı 10,26 mm2; Grup II'de 10,32 mm2 olarak hesapladık. Sonuç: Bu sonuç ile mediyan sinir alanının yaşla birlikte artmadığını ve mediyan sinirin bası altında kalmasının başka sebepleri olabileceğini düşünmekteyiz. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Mediyan Sinir Alanının Manyetik Rezonans Görüntüleme ile İncelenmesi